Application of the Storytelling Method in a Service Company to Provide Client Satisfaction: A Study on Sibambo Studio House Architecture Bureau - Muhammad Yanuar Abdulloh; Kartika Anggraeni Sudiono Putri (Ekonomis: Journal of Economics and Business, 2023)
This research aims to analyze the application of the storytelling method in service companies in providing satisfaction to clients, a case study at the House Architecture Bureau with the brand name Sibambo Studio. A descriptive qualitative method with a case study approach is used in this research to describe in detail how storytelling can be used as an effective communication tool between service companies and clients. This research involved interviews with employees and clients of Sibambo Studio's House Architecture Bureau, observation, and documentation analysis to obtain data and information related to the application of the storytelling method which was then explained by research informants including the marketing team (chief marketing officer and sales marketing), architect team (architect in charge and interior architect) and service user clients. The data analysis process was carried out through data reduction, data presentation, and summarizing the results. The research findings show that the application of the storytelling method has a positive impact on client satisfaction. In this context, storytelling is used as a tool to communicate values in the design by adjusting the needs and expectations of the client. Stories that are translated into appropriate designs and detailed explanations help describe the experience desired by the client. Through stories, clients can feel more involved in their home design process and feel heard by the company. This affects how high the client's level of satisfaction, trust, and emotional bond with the company is.